2006
DOI: 10.1038/sj.bjp.0706640
|View full text |Cite
|
Sign up to set email alerts
|

Activation of insulin‐like growth factor I receptor‐mediated pathway by ginsenoside Rg1

Abstract: 1 Ginsenoside Rg1, an active ingredient in ginseng, was previously shown to be a novel class of potent phytoestrogen. The present study aims at investigating the molecular mechanisms involved in mediating its actions in human breast cancer (MCF-7) cells. 2 Rg1 (1 pM) stimulates cell proliferation (Po0.01) and estrogen-responsive pS2 mRNA expression (Po0.05) without alteration of estrogen receptor alpha (ERa) protein or mRNA expression in MCF-7 cells. In addition, 10 À14 -10 À4 M of Rg1 does not demonstrate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Ginsenoside Rg1 can stimulate the growth of human breast cancer MCF-7 cells as well as activate estrogen response element-dependent luciferase activities (Chan et al, 2002). Furthermore, we have demonstrated that ginsenoside Rg1 could activate the insulin-like growth factor-I receptor (IGF-IR) signaling pathway through enhancing tyrosine phosphorylation of insulin receptor substrate-1 in MCF-7 cells (Chen et al, 2006). These results suggest that the growth factor signaling pathway is involved in the action of ginsenoside Rg1.…”
Section: Introductionmentioning
confidence: 88%
“…Ginsenoside Rg1 can stimulate the growth of human breast cancer MCF-7 cells as well as activate estrogen response element-dependent luciferase activities (Chan et al, 2002). Furthermore, we have demonstrated that ginsenoside Rg1 could activate the insulin-like growth factor-I receptor (IGF-IR) signaling pathway through enhancing tyrosine phosphorylation of insulin receptor substrate-1 in MCF-7 cells (Chen et al, 2006). These results suggest that the growth factor signaling pathway is involved in the action of ginsenoside Rg1.…”
Section: Introductionmentioning
confidence: 88%
“…It has been safely being used in China for more than 2000 years as a tonic against stress. Ginsenosides (steroidal glycosides), in the extracts of various kinds of ginsengs, are the major active components responsible for the pharmacological effects of ginseng on the central nervous, cardiovascular, endocrine, and immune systems [1][2][3][4][5][6] . There are 2 major classes of ginsenosides, protopanaxatriols (Rg1, Rg2, Re, and Rf) and protopanaxadiols (Rb1, Rb2, Rc, and Rd).…”
Section: Introductionmentioning
confidence: 99%
“…21,31 In fact, ginsenoside Rg1 was recently shown to stimulate MCF-7 cell proliferation and pS2 mRNA expression through activation of cross-talk between ER-and insulin growth factor 1 receptor-dependent pathways. 31 Ginsenoside Rb1-induced estrogenic effects in MCF-7 cells also may or may not be mediated by direct interaction with ER. 23,24 The current study addressed the possibility that the extraction method used to extract ginseng will dictate the potential estrogenicity of ginseng products.…”
Section: Discussionmentioning
confidence: 99%